Visual Correlates of Static (form) Threshold and Motion Coherence Threshold. - Shayler, Geoff; Pereira, Stephen (Optometry & Visual Performance, 2016)
Background: In order to characterize visual responses to cortical function, the "ball in the grass" test was used within an optometric practice environment to measure static (form) coherence thresholds and motion coherence thresholds in children presenting for a routine eyesight examination. This testing identified differences in function between children acknowledged as having educational difficulties compared to those without such a label. Methods: We showed direct relationships of neurological processing, as measured with this test, compared to a number of optometric measures of near visual processing. Analysis was carried out to investigate the effects of using both stress relieving lenses (SRLs) and optometric vision therapy. Results: These studies indicated significant improvement in cortical processing, associated with improved visual skills, with both SRLs and optometric vision therapy.